2009
DOI: 10.1002/app.30785
|View full text |Cite
|
Sign up to set email alerts
|

Residual monomer in superabsorbent polymers: Effects of the initiating system

Abstract: Minimized residual monomer is an essential requirement particularly in hygienic, pharmaceutical, and food packaging polymer products such as superabsorbent polymers (SAPs). The present article is the first non-patent report on the study of a highly effective polymerization variable (e.g. initiator) on the residual monomer of SAPs based on partially neutralized acrylic acid. Two persulfate systems, i.e. ammonium persulfate (APS)/sodium metabisulfite (SMBS) and APS/tetramethyl ethylenediamine (TMEDA), were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Quicker gelation has negative effect respecting to the residual monomer content. According to our previous study, the higher the gelation time, the lower the residual monomer will be 8. A phase conversion from liquid to solid is occurred at gelation point which causes to decrease probability of collision of free radials to unreacted monomers due to lower diffusion in the semisolid (gelled) medium 8…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Quicker gelation has negative effect respecting to the residual monomer content. According to our previous study, the higher the gelation time, the lower the residual monomer will be 8. A phase conversion from liquid to solid is occurred at gelation point which causes to decrease probability of collision of free radials to unreacted monomers due to lower diffusion in the semisolid (gelled) medium 8…”
Section: Resultsmentioning
confidence: 96%
“…There are nearly 1200 nonpatent articles on superabsorbents published during years 1976–2009. However, except for a recent paper,8 none of them investigated effect of fundamental parameters on the SAP residual monomer content as a key characteristic especially for those used in hygienic, medical, pharmaceutical, and food packaging applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of residual monomer in any hydrogel product is dependent on the reaction conditions, type and concentration of initiator, monomer, reaction temperature, and so on [23]. For instance, it was found that the rate at which the initiator dissociates can change the concentration of the residual monomer to a great extent [120]. Hydrogel composites containing high concentration of clay may show increased swelling and hence decreased gel strength [80].…”
Section: Properties Of Hydrogel Composites and Nanocompositesmentioning
confidence: 99%